Sex Differences in Blood Pressure and Potential Implications for Cardiovascular Risk Management - Picone, Dean S.; Stoneman, Elif; Cremer, Antoine; Schultz, Martin G.; Otahal, Petr; Hughes, Alun D.; Black, J. Andrew; Bos, Willem Jan; Chen, Chen Huan; Cheng, Hao Min; Dwyer, Nathan; Lacy, Peter; et al. (Hypertension, 2023)
BACKGROUND: Accurate blood pressure (BP) measurement is critical for optimal cardiovascular risk management. Age-related trajectories for cuff-measured BP accelerate faster in women compared with men, but whether cuff BP represents the intraarterial (invasive) aortic BP is unknown. This study aimed to determine the sex differences between cuff BP, invasive aortic BP, and the difference between the 2 measurements. METHODS: Upper-arm cuff BP and invasive aortic BP were measured during coronary angiography in 1615 subjects from the Invasive Blood Pressure Consortium Database. This analysis comprised 22 different cuff BP devices from 28 studies. RESULTS: Subjects were 64±11 years (range 40-89) and 32% women. For the same cuff systolic BP (SBP), invasive aortic SBP was 4.4 mm Hg higher in women compared with men. Cuff and invasive aortic SBP were higher in women compared with men, but the sex difference was more pronounced from invasive aortic SBP, was the lowest in younger ages, and the highest in older ages. Cuff diastolic blood pressure overestimated invasive diastolic blood pressure in both sexes. For cuff and invasive diastolic blood pressure separately, there were sex*age interactions in which diastolic blood pressure was higher in younger men and lower in older men, compared with women. Cuff pulse pressure underestimated invasive aortic pulse pressure in excess of 10 mm Hg for both sexes in older age. CONCLUSIONS: For the same cuff SBP, invasive aortic SBP was higher in women compared with men. How this translates to cardiovascular risk prediction needs to be determined, but women may be at higher BP-related risk than estimated by cuff measurements.
CRIS-Team Scopus Importer:2023-01-27
Keywords: diagnostic equipment; hypertension; physiology; pulse wave analysis; sex factors